Bidirectional crosstalk between microglia and serotonin signaling in neuroinflammation and CNS disorders - Yangchen Zheng; Limin Xu; Limin Xu (Frontiers in Immunology)
Neuroinflammatory processes are increasingly recognized as central to the pathophysiology of diverse central nervous system (CNS) disorders, including major depressive disorder (MDD), Alzheimer’s disease (AD), and Parkinson’s disease (PD). Microglia, the resident immune effector cells of the CNS, are key regulators of neuroimmune responses and engage in bidirectional communication with the serotonergic system. Activation of microglia toward a pro-inflammatory phenotype can disrupt serotonergic neurotransmission by altering the expression and function of the serotonin transporter (SERT) and modulating downstream 5-HT receptor signaling pathways. Conversely, serotonergic neurotransmission—mediated through receptor subtypes such as 5-HT1A, 5-HT2A/2B, and 5-HT7—can regulate microglial phenotypic polarization and cytokine production, thereby influencing the inflammatory milieu and CNS homeostasis. This review synthesizes current evidence on the dynamic interplay between microglial activation states and serotonergic signaling, emphasizing their mutual contributions to disease onset and progression. Furthermore, we examine the therapeutic potential of targeting this neuroimmune interface using pharmacological strategies, including selective serotonin reuptake inhibitors (SSRIs), anti-inflammatory agents, and receptor-specific ligands. Clarifying this bidirectional crosstalk may inform the development of innovative interventions for neuroinflammation-associated neuropsychiatric and neurodegenerative disorders.